High-Performance Regular Perovskite Solar Cells Employing Low-Cost Poly(ethylenedioxythiophene) as a Hole-Transporting Material - Jiang, Xiaoqing (Sci Rep, 2017)
Herein, we successfully applied a facile in-situ solid-state synthesis of conducting polymer poly(3,4-ethylenedioxythiophene) (PEDOT) as a HTM, directly on top of the perovskite layer, in conventional mesoscopic perovskite solar cells (PSCs) (n-i-p structure). The fabrication of the PEDOT film only involved a very simple in-situ solid-state polymerisation step from a monomer 2,5-dibromo-3,4-ethylenedioxythiophene (DBEDOT) made from a commercially available and cheap starting material. The ultraviolet photoelectron spectroscopy (UPS) demonstrated that the as-prepared PEDOT film possesses the highest occupied molecular orbital (HOMO) energy level of −5.5 eV, which facilitates an effective hole extraction from the perovskite absorber as confirmed by the photoluminescence measurements. Optimised PSC devices employing this polymeric HTM in combination with a low-cost vacuum-free carbon cathode (replacing the gold), show an excellent power conversion efficiency (PCE) of 17.0% measured at 100 mW cm(−2) illumination (AM 1.5G), with an open-circuit voltage (V(oc)) of 1.05 V, a short-circuit current density (J(sc)) of 23.5 mA/cm(2) and a fill factor (FF) of 0.69, respectively. The present finding highlights the potential application of PEDOT made from solid-state polymerisation as a HTM for cost-effective and highly efficient PSCs.